Analisis potensi limbah kelapa sawit untuk pakan ternak ruminansia di PT Medcopapua Hijau Selaras Sidey Manokwari - Novita Sari Ojaba; Marlyn N. Lekitoo; Sientje D. Rumetor (Cassowary, 2021)
This research aimed to investigate and analyzing the potential of palm waste based on the type and amount of waste the quality of waste for as ruminant feed. Research conducted at PT MedcoPapua Hijau Selaras Sidey Manokwari lasts from 2 september until 3 october 2019. The results get potential of waste palm at PT MedcoPapua Hijau Selaras Sidey have relative large are empty bunches, 112,2 tons/day, fibers 28,36 tons/day, shell, 28,94 tons/days and liquid waste, oil sludge 24,80 tons/day, waste that can be utilized as a ruminant feed, there has content of BK and BO which good is every each, empty bunches (BK 91,95%. BO 81,84%) Fibers (BK 92, 16 %, BO 93,83%), Shell ( BK 91,51. BO 75,01 %), Oil Sludge (BK 23,90%. BO 83,78%).